1) =0,4х-1+6х+3,6=6,4х+2,6, если х = 0,4, то 6,4*0,4+2,6=5,16
2) =1,5х-1+2,8-4,2х=1,8-2,7х, при х= -0,2 1,8-2,7*(-0,2)= 1,8+0,54=2,34
3)=1,2х-1,8+3,6х-5,4=4,8х-7,2, при х=-0,1 4,8*(-0,1)-7,2=-0,48-7,2=-7,68
4)5-2(3х-4)=4х-3 5)3-4(2х-5)=2-6х 6)6-3 (2х-5)=2х-7
5-6х+8=4х-3 3-8х+20=2-6х 6-6х+15=2х-7
16=10х 21=2х 28=8х
х=1,6 х=10,5 х=3,5
7)9-2(3х-4)=3х+8 8)11+4 (х-3)=9х- 15
9-6х+8=3х+8 11+4х-12= 9х-15
9=9х 14=5х
х=1 х=2,8
x=4
Объяснение:
(x-4)/5=1-(x-1)/3
(x-4)/5=(3-x+1)/3
(x-4)/5=(4-x)/3
3(x-4)=5(4-x)
3x-12=20-5x
3x+5x=20+12
8x=32
x=32:8
x=4